ICE BREAKING DALAM PROSES BELAJAR MENGAJAR: learning, routinity, boring, ice breaking - Achmad Fanani (Buana Pendidikan, 2010)
In general, teacher’s main job is to plan, guide, and evaluate the teaching and learning process. However, it is not as easy as the teacher thinks it is as he or she may face some challenges. Though he or she has carried out his or her job, he or she cannot yield an optimum result. One factor deals with the learning environment. An unsupportive learning environment may affect the physical and psychological aspects of students. This may result in the students’ fatigue and it influences their cognitive development and creativity which in turn affect their learning achievement. Ice breaking is an activity which can overcome those problems. The current article addresses the types and how ice breaking is implemented to enhance the quality of learning itself.